Comparison of the respiratory effects of commonly utilized general anaesthesia regimes in male Sprague-Dawley rats - Ballók, Bence; Schranc, Álmos; Tóth, Ibolya; Somogyi, Petra; Tolnai, József; Peták, Ferenc; Fodor, Gergely H. (Frontiers in Physiology, 2023)
Background: Respiratory parameters in experimental animals are often characterised under general anaesthesia. However, anaesthesia regimes may alter the functional and mechanical properties of the respiratory system. While most anaesthesia regimes have been shown to affect the respiratory system, the effects of general anaesthesia protocols commonly used in animal models on lung function have not been systematically compared. Methods: The present study comprised 40 male Sprague-Dawley rats divided into five groups (N=8 in each) according to anaesthesia regime applied: intravenous (iv) Na-pentobarbital, intraperitoneal (ip) ketamine-xylazine, iv propofol-fentanyl, inhaled sevoflurane, and ip urethane. All drugs were administered at commonly used doses. End-expiratory lung volume (EELV), airway resistance (Raw) and tissue mechanics were measured in addition to arterial blood gas parameters during mechanical ventilation while maintaining positive end-expiratory pressure (PEEP) values of 0, 3 and 6 cmH2O. Respiratory mechanics were also measured during iv methacholine (MCh) challenges to assess bronchial responsiveness. Results: While PEEP influenced baseline respiratory mechanics, EELV and blood gas parameters (p<0.001), no between-group differences were observed (p>0.10). Conversely, significantly lower doses of MCh were required to achieve the same elevation in Raw under ketamine-xylazine anaesthesia compared to the other groups. Conclusions: In the most frequent rodent model of respiratory disorders, no differences in baseline respiratory mechanics or function were observed between commonly used anaesthesia regimes. Bronchial hyperresponsiveness in response to ketamine-xylazine anaesthesia should be considered when designing experiments using this regime. The findings of the present study indicate commonly used anaesthetic regimes allow fair comparison of respiratory mechanics in experimental animals undergoing any of the examined anaesthesia protocols.